Lithium-philic current collector for lithium metal battery as well as preparation method and application of lithium-philic current collector

By using the lithium collector in a lithium metal battery, it contains the copper stack layer and spherical particles of the film -shaped coin -shaped coin -shaped coin -shaped banks, which solves the growth of lithium branches crystal, and improves the electrochemical performance and service life of the battery.

CN119381459AActive Publication Date: 2025-01-28HEFEI UNIV OF TECH
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411496723.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2025-01-28
Estimated Expiration
2044-10-24

AI Technical Summary

Technical Problem

The problem of uncontrollable growth of lithium dendrites during the deposition process of lithium metal batteries and the resulting safety problems are difficult to effectively solve in the prior art.

Method used

A lithium lithium collector is used, including a collecting of a stacking coating of the stacking layer of the collection of a collection of a stacking of a collection of a collection of the stacking coat, the spherical shape of the silver reaction of the lithium and the stacking layer on the stack layer. Granules. The streaming body forms a lithium layer on copper foil or foam copper by preparing methods to inhibit the growth of lithium branches crystals.

Benefits of technology

Effectively suppress the growth of lithium branches, improve the electrochemical properties of lithium metal batteries, improve the efficiency of Kuron, extend the service life of the battery, and reduce production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381459A_ABST
    Figure CN119381459A_ABST
Patent Text Reader

Abstract

The invention discloses a lithium-loving current collector for a lithium metal battery as well as a preparation method and application of the lithium-loving current collector. The lithium-loving current collector comprises a current collector substrate (copper foil or foamy copper), a flaky silver-coated copper stacking layer loaded on the surface of the current collector substrate, and spherical particles loaded on the stacking layer through reaction of lithium and silver in the stacking layer. When the lithium-loving current collector is applied to a lithium metal battery, a relatively good homogenization effect can be achieved on lithium deposition, and the growth of lithium dendrites is effectively inhibited.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium metal batteries, and in particular to a lithium-philic current collector for lithium metal batteries and a preparation method and application thereof. Background Art

[0002] The energy density of lithium-ion batteries with graphite as negative electrode has reached its limit, and it is urgent to develop new battery systems to meet the market demand for high energy density energy storage devices. -1 ) and the lowest redox potential (-3.04V compared to the standard hydrogen electrode), the lithium metal battery formed by it with any positive electrode material has a higher energy density than commercial lithium-ion batteries, so it can better address the market demand for high energy density.

[0003] However, the problem of uncontrollable growth of lithium dendrites during the deposition process of lithium metal anode and the resulting safety issues have yet to be resolved. In recent years, researchers have developed many strategies to solve the above problems, such as electrolyte component design, solid electrolytes, and current collector modification. The strategy of in-situ generation of a solid electrolyte interface on a lithium metal anode by adjusting the ratio of lithium salt and solvent in the electrolyte or adding various electrolyte additives is simple and effective. However, the mechanical strength of this in-situ generated solid electrolyte interface is often unable to withstand the volume expansion of lithium, so the performance of lithium metal batteries cannot be effectively improved in the long term. Solid electrolytes can significantly inhibit the volume expansion and dendrite growth of lithium metal anodes due to their high mechanical modulus, but problems such as low intrinsic ionic conductivity and poor mechanical contact caused by solid interfaces remain to be solved. Among these strategies, current collector modification is considered to be a simple, effective and easy-to-scale strategy for achieving long-term protection of lithium metal anodes because it can alleviate the concentration of local current density and make lithium insertion / stripping behavior uniform. Summary of the invention

[0004] In view of the problems existing in the prior art, the present invention proposes a lithium-philic current collector for lithium metal batteries and a preparation method and application thereof, aiming to improve the electrochemical performance of lithium metal batteries by preparing a current collector that inhibits the growth of lithium dendrites.

[0005] To achieve the purpose, the present invention adopts the following technical solution:

[0006] The present invention first provides a lithium-philic current collector for a lithium metal battery, comprising a current collector substrate, a sheet-like silver-copper stacking layer loaded on the surface of the current collector substrate, and spherical particles loaded on the stacking layer by the reaction of lithium with silver in the stacking layer; wherein the current collector substrate is copper foil or foam copper.

[0007] The present invention also provides a method for preparing the lithium-philic current collector for the lithium metal battery, the specific steps of which are as follows:

[0008] Step 1, adding flaky silver-coated copper powder to deionized water, ultrasonically dispersing for 20 to 40 minutes at room temperature, and then magnetically stirring for 20 to 40 minutes to obtain a silver-coated copper dispersion;

[0009] Step 2, adding a binder to the silver-coated copper dispersion, stirring magnetically for 2 to 4 hours at room temperature, and then ultrasonically treating for 20 to 40 minutes to obtain a uniform mixed solution;

[0010] Step 3, loading the mixed solution obtained in step 2 on the surface of the current collector substrate, and drying it by forced air at 60 to 90° C. for 2 to 4 hours, so that a sheet-like silver-coated copper stacking layer is formed on the surface of the current collector substrate;

[0011] Step 4: Assemble an electrolytic cell with the current collector substrate treated in step 3 as the cathode and the lithium sheet as the anode, and use a charge and discharge tester at a current density of 0.4 to 0.6 mA cm -2 Under the condition of electroplating 0.1-0.5 mAh cm -2 The metallic lithium is used to load spherical particles on the stacking layers to obtain a lithium-philic current collector for lithium metal batteries.

[0012] Furthermore, in step 1, the silver content of the flaky silver-coated copper powder is 1-5%.

[0013] Furthermore, in step 1, the mass ratio of the flaky silver-coated copper powder to deionized water is 1:1-3.

[0014] Furthermore, in step 2, the binder is hydroxypropyl methylcellulose, the molecular weight of which is 80,000 to 120,000, and the mass ratio of the binder to the flaky silver-coated copper powder is 1:40 to 60.

[0015] Furthermore, in step 3, the mixed solution is loaded on the surface of the current collector substrate by a blade coating method or a vacuum impregnation method. When copper foil is used as the current collector substrate, the blade coating method is used, and the operation steps are: drop the mixed solution obtained in step 2 onto the surface of the copper foil, and adjust the gap between the blade and the copper foil to achieve surface loading of the copper foil. When copper foam is used as the current collector substrate, the vacuum impregnation method is used, and the operation steps are: immerse the copper foam in the mixed solution obtained in step 2 and evacuate to vacuum, and take it out after maintaining the pressure for 3 to 7 minutes, so as to achieve surface loading of the copper foam.

[0016] Furthermore, in step 4, the electrolyte added to the electrolytic cell is a mixed solution of DOL and DME in a volume ratio of 1:1 containing 1M LiTFSI, and LiNO3 with a mass concentration of 1% is added as an additive.

[0017] The present invention also provides a lithium metal battery, comprising the lithium-philic current collector.

[0018] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0019] 1. The lithium-philic current collector is a lithium-philic layer designed on copper foil or foam copper. The lithium-philic layer is composed of a sheet-like silver-coated copper stacking layer and spherical particles loaded on the stacking layer, wherein: the sheet-like stacking layer provides a three-dimensional space for the deposition of lithium, effectively reducing the local current density, and the spherical particles provide a nucleation basis for the deposition of lithium, so that lithium can be deposited evenly. When the current collector is used in a lithium metal battery, it can effectively inhibit the growth of lithium dendrites.

[0020] 2. Hydroxypropyl methylcellulose is used as a binder to avoid the use of organic solvents, effectively alleviate the environmental pressure caused by the use of organic solvents, and save production costs to a certain extent.

[0021] 3. The battery assembled using the lithium-philic current collector exhibits a higher coulombic efficiency, which is beneficial to improving the cycle stability and service life of lithium metal secondary batteries, thereby effectively promoting the commercialization process of lithium metal batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a scanning electron microscope image of the lithium-philic current collector prepared in Example 1.

[0023] Figure 2 This is the X-ray diffraction pattern of the lithium-philic current collector prepared in Example 1.

[0024] Figure 3 To deposit 3 mAh cm on the surface of the current collector prepared in Example 1 -2 Scanning electron micrograph of the surface after lithium deposition.

[0025] Figure 4 This is a coulombic efficiency diagram of the current collectors of Example 1, Comparative Example 1 and Comparative Example 2 after being assembled into a lithium metal battery.

[0026] Figure 5 This is a diagram of the coulombic efficiency of the current collector of Example 2 after being assembled into a lithium metal battery.

[0027] Figure 6 To deposit 3 mAh cm on the surface of the current collector prepared in Comparative Example 1 -2 Scanning electron micrograph of the surface after lithium deposition.

[0028] Figure 7 To deposit 3 mAh cm on the surface of the current collector prepared in Comparative Example 2 -2 Scanning electron micrograph of the surface after lithium deposition. DETAILED DESCRIPTION

[0029] The technical solution of the present invention is further described and explained below in conjunction with embodiments, but these embodiments are not intended to limit the protection scope of the present invention.

[0030] Example 1

[0031] This embodiment provides a method for preparing a lithium-philic current collector for a lithium metal battery, comprising the following steps:

[0032] Step 1: Add 1 g of commercially available flaky silver-coated copper powder with a silver content of 3% to 1 g of deionized water, disperse it ultrasonically at room temperature for 30 minutes, and then stir it magnetically for 30 minutes to obtain a silver-coated copper dispersion.

[0033] Step 2: Take 0.02 g of hydroxypropyl methylcellulose powder with a molecular weight of 100,000 and add it to the silver-coated copper dispersion. After magnetic stirring for 3 hours at room temperature, ultrasonic treatment is performed for 30 minutes to obtain a uniform mixed solution.

[0034] Step 3: drop the uniform mixed liquid obtained in step 2 onto the surface of the copper foil, adjust the gap between the scraper and the copper foil to achieve surface loading of the copper foil, and dry it at 80°C for 3 hours to form a flaky silver-coated copper stacking layer on the surface of the current collector substrate.

[0035] Step 4: Assemble an electrolytic cell using the current collector substrate treated in step 3 as the cathode, the lithium sheet as the anode, and a mixed solution of DOL and DME in a volume ratio of 1:1 containing 1M LiTFSI and added with 1% LiNO3 as the electrolyte. Use a charge and discharge tester at a current density of 0.5 mA cm -2 Under the condition of 0.5 mAh cm -2 The metallic lithium is used to load spherical particles on the stacking layer to obtain a lithium-philic current collector.

[0036] Step 5: Preparation of lithium metal battery

[0037] Under the protection of an argon atmosphere glove box, the obtained lithium-philic current collector was matched with lithium metal to assemble into a half-cell. The diaphragm used was a polypropylene diaphragm, the electrolyte composition was a mixed solution of 1M LiTFSI dissolved in DOL / DME (volume ratio of 1:1) (and 1% mass concentration of LiNO3 was added as an additive), and the electrolyte injection volume was 50μL.

[0038] Figure 1 This is a scanning electron microscope image of the lithium-philic current collector prepared in Example 1. The results show that a lithium-philic layer consisting of a sheet-like stacked layer and spherical particles on the stacked layer is successfully prepared on the surface of the copper foil substrate. Figure 2The X-ray diffraction pattern of the lithium-philic current collector prepared in Example 1 shows that on the surface of the copper foil substrate, the sheet-like stacking layer and the spherical particles on the stacking layer are mainly composed of Cu, Ag3Li 10 And Li.

[0039] In order to study the effect of the lithium-philic current collector on the lithium deposition morphology, Figure 3 The deposition rate of 3 mAh cm on the current collector surface in this example is given. -2 Surface scanning electron microscopy image after lithium (3mAh cm -2 Under the test conditions, 3 mAh cm was deposited on the current collector of the lithium metal battery. -2 The battery was then disassembled, taken out and used for SEM observation), and it was found that the lithium deposition was a dense block morphology rather than dendritic lithium, which indicates that the lithium-philic current collector has a good regulating effect on lithium deposition.

[0040] Figure 4 The coulombic efficiency diagram of the current collector of Example 1 after being assembled into a lithium metal battery. It can be seen that at 0.5 mA cm -2 ,0.5mAh cm -2 Under the test conditions, the lithium metal battery based on the lithium-philic current collector showed the best cycling performance, that is, it can maintain a high coulombic efficiency (98.2%) even at a longer number of cycles (500 cycles). This shows that the lithium-philic layer composed of the lamellar stacking layer and the spherical particles on the stacking layer can have a good uniform effect on the deposition of lithium and effectively inhibit the growth of lithium dendrites.

[0041] Example 2

[0042] This embodiment provides a method for preparing a lithium-philic current collector for a lithium metal battery, comprising the following steps:

[0043] Step 1: Add 0.8 g of commercially available flaky silver-coated copper powder with a silver content of 3% to 1 g of deionized water, disperse it ultrasonically at room temperature for 30 minutes, and then stir it magnetically for 30 minutes to obtain a silver-coated copper dispersion.

[0044] Step 2: Take 0.016 g of hydroxypropyl methylcellulose powder with a molecular weight of 100,000 and add it to the silver-coated copper dispersion. Continue magnetic stirring at room temperature for 3 hours, and then ultrasonically treat for 30 minutes to obtain a uniform mixed solution.

[0045] Step 3, immerse the foam copper in the uniform mixed solution obtained in step 2 and evacuate to vacuum, take it out after maintaining the pressure for 5 minutes, so as to achieve the surface loading of the foam copper, and blow dry it at 80°C for 3 hours to form a flaky silver-coated copper stacking layer on the surface of the collector substrate.

[0046] Step 4: Assemble an electrolytic cell using the current collector substrate treated in step 3 as the cathode, the lithium sheet as the anode, and a mixed solution of DOL and DME in a volume ratio of 1:1 containing 1M LiTFSI and added with 1% LiNO3 as the electrolyte. Use a charge and discharge tester at a current density of 0.5 mA cm -2 Under the condition of electroplating 0.1 mAh cm -2 After adding metallic lithium, spherical particles are loaded on the stacked layers to obtain a lithium-philic current collector.

[0047] Step 5: Preparation of lithium metal battery

[0048] Under the protection of an argon atmosphere glove box, the obtained lithium-philic current collector was matched with lithium metal to assemble into a half-cell. The diaphragm used was a polypropylene diaphragm, the electrolyte composition was a mixed solution of 1M LiTFSI dissolved in DOL / DME (volume ratio of 1:1) (and 1% mass concentration of LiNO3 was added as an additive), and the electrolyte injection volume was 50μL.

[0049] Figure 5 The coulombic efficiency diagram of the current collector of Example 2 after being assembled into a lithium metal battery is given. It can be seen that at 0.5 mA cm -2 ,0.5mAh cm -2 Under the test conditions, the lithium metal battery based on the lithium-philic current collector maintained a relatively stable cycle performance. After 150 cycles, its coulombic efficiency was still as high as 98.3%.

[0050] Comparative Example 1

[0051] The difference from Example 1 is that the surface of the copper foil substrate is not modified, and the bare copper foil is directly used to assemble the lithium metal battery.

[0052] Figure 6 The surface deposition of 3 mAh cm on the current collector in Comparative Example 1 is given. -2 From the scanning electron microscope image of the surface after lithium deposition, it can be found that the deposition morphology of lithium is obviously dendritic. Figure 4 It can be seen that the coulombic efficiency of the lithium metal battery corresponding to Comparative Example 1 is only 79.1% after 100 cycles, which indicates that serious lithium dendrite growth and loss of inactive lithium occurred during the cycle, thus leading to the deterioration of the cycle performance of the lithium metal battery.

[0053] Comparative Example 2

[0054] The difference from Example 1 is that the commercially available flaky copper powder not containing silver is used in step 1, and the obtained current collector is used for assembling a lithium metal battery.

[0055] Figure 7The deposition rate of 3 mAh cm on the current collector surface in Comparative Example 2 is given. -2 The surface scanning electron microscope image after lithium deposition shows that the deposition uniformity of lithium is poor and dendritic lithium is still generated. Figure 4 It can be seen that the coulombic efficiency of the lithium metal battery corresponding to Comparative Example 2 is 93.2% after 100 cycles, which still cannot reach the level of the coulombic efficiency corresponding to Example 1.

[0056] The above embodiments are only used to explain the present invention, and are intended to illustrate the technical concept and features of the present invention, and do not constitute any limitation to the present invention. For those skilled in the art, various changes and modifications can be made to the present invention without departing from the principles and spirit of the present invention, and these changes and modifications should also be regarded as the protection scope of the present invention.

Claims

1. A lithium-philic current collector for a lithium metal battery, characterized in that: It includes a current collector matrix, a sheet-like silver-coated copper stacking layer loaded on the surface of the current collector matrix, and spherical particles loaded on the stacking layer due to the reaction between lithium and silver in the stacking layer; wherein the current collector matrix is ​​copper foil or foam copper.

2. A method for preparing the lithium-philic current collector for lithium metal batteries according to claim 1, characterized in that: Here are the steps: Step 1, adding flaky silver-coated copper powder to deionized water, ultrasonically dispersing for 20 to 40 minutes at room temperature, and then magnetically stirring for 20 to 40 minutes to obtain a silver-coated copper dispersion; Step 2, adding a binder to the silver-coated copper dispersion, stirring magnetically for 2 to 4 hours at room temperature, and then ultrasonically treating for 20 to 40 minutes to obtain a uniform mixed solution; Step 3, loading the mixed solution obtained in step 2 on the surface of the current collector substrate, and drying it by forced air at 60 to 90° C. for 2 to 4 hours, so that a sheet-like silver-coated copper stacking layer is formed on the surface of the current collector substrate; Step 4: Assemble an electrolytic cell with the current collector substrate treated in step 3 as the cathode and the lithium sheet as the anode, and use a charge and discharge tester at a current density of 0.4 to 0.6 mA cm -2 Under the condition of electroplating 0.1-0.5 mAh cm -2 The metallic lithium is used to load spherical particles on the stacking layers to obtain a lithium-philic current collector for lithium metal batteries.

3. The preparation method according to claim 2, characterized in that: In step 1, the silver content of the flaky silver-coated copper powder is 1-5%.

4. The preparation method according to claim 2, characterized in that: In step 1, the mass ratio of the flaky silver-coated copper powder to deionized water is 1:1-3.

5. The preparation method according to claim 2, characterized in that: In step 2, the binder is hydroxypropyl methylcellulose, and its molecular weight is 80,000 to 120,000.

6. The preparation method according to claim 2, characterized in that: In step 2, the mass ratio of the binder to the flaky silver-coated copper powder is 1:40-60.

7. The preparation method according to claim 2, characterized in that: In step 3, the mixed solution is loaded on the surface of the current collector substrate by a doctor blade coating method or a vacuum impregnation method.

8. The preparation method according to claim 7, characterized in that: When copper foil is used as the current collector substrate, a scraper coating method is used, and the operation steps are: dripping the mixed solution obtained in step 2 onto the surface of the copper foil, and adjusting the gap between the scraper and the copper foil to achieve surface loading on the copper foil; When copper foam is used as the current collector matrix, a vacuum impregnation method is used, and the operating steps are: immerse the copper foam in the mixed solution obtained in step 2 and evacuate to vacuum, and take it out after maintaining the pressure for 3 to 7 minutes, so as to achieve surface loading of the copper foam.

9. The preparation method according to claim 3, characterized in that: In step 4, the electrolyte added to the electrolytic cell is a mixed solution of DOL and DME in a volume ratio of 1:1 containing 1M LiTFSI, and LiNO3 with a mass concentration of 1% is added as an additive.

10. A lithium metal battery, characterized in that: It comprises the lithium-philic current collector as claimed in claim 1.

Citation Information

Patent Citations

  • Preparation method of battery positive plate, positive plate and lithium ionic cell

    CN101162773A

  • Method for preparing lithium ion battery aqueous binder cathode paste

    CN110311139A

  • Three-dimensional current collector for inhibiting lithium metal negative electrode dendrites and application of three-dimensional current collector in metal lithium battery

    CN111668493A

  • Modified copper current collector for negative electrode of lithium metal battery and preparation method of modified copper current collector

    CN114464814A

  • Positive electrode, lithium battery including positive electrode, and method of manufacturing positive electrode

    CN114843457A